Mesoporous silica fluorescent probe based on surface ion imprinting technology and application thereof

The preparation of phenanthroline-modified mesoporous silica nanofluorescent probes through surface ion blotting technology solves the problem of limited selectivity for nanocomposite fluorescent probe detection, realizes high selectivity fluorescence detection and adsorption removal of copper ions in water, and is environmentally friendly in aqueous solutions.

CN119775995AInactive Publication Date: 2025-04-08JIANGSU OCEAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411915595.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, the detection selectivity of nanocomposite fluorescence probes for target heavy metal ions is limited, and small molecule fluorescence probes are difficult to directly dissolve in water, which increases the environmental burden.

Method used

Surface ion blotting technology is used to prepare phenanthroline modified mesoporous silica nanofluorescent probes. By forming a specific phenanthroline blotting cavity on the surface of mesoporous silica, selective identification, fluorescence detection and adsorption removal of copper ions in water can be achieved.

Benefits of technology

The material's selectivity for the quantitative detection and adsorption removal of fluorescence of copper ions in water is improved, and the problem of limited selectivity for nanocomposite fluorescence probe detection is solved, and environmentally friendly fluorescence probe application is realized in aqueous solution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775995A_ABST
    Figure CN119775995A_ABST
Patent Text Reader

Abstract

The invention discloses a phenanthroline-modified mesoporous silica fluorescent probe based on a surface ion imprinting technology and application of the phenanthroline-modified mesoporous silica fluorescent probe. The phenanthroline-modified mesoporous silica fluorescent probe is prepared by the following steps: firstly, forming a metal complex functional monomer by using a siloxane coupling agent containing a phenanthroline fluorescent chromophore and template copper ions; a copper ion complex film is formed on the surface of mesoporous silica by using a sol-gel process, copper ions can leave a specific imprinting cavity after strong acid elution, and the cavity and a template copper ion object have relatively high complementarity in shape and size; the surface ion imprinting technology is used, so that the action selectivity of phenanthroline and target ions can be remarkably improved, and the prepared mesoporous silica nano fluorescent probe can be used for selective fluorescence detection and adsorption removal of copper ions in a water body.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of organic functional modification of nano-mesoporous silica surface, and in particular to a phenanthroline-modified mesoporous silica fluorescent probe based on ion imprinting technology and application thereof, for realizing selective fluorescent detection and adsorption removal of copper ions in water. Background Art

[0002] Although copper is a trace element in biological systems, once it exceeds the normal concentration range, it may pose a potential threat to human health and the ecological environment. Excessive intake of copper ions will cause physical disasters, including symptoms such as nausea, vomiting, and diarrhea, and long-term exposure may cause serious damage to the nervous system and liver. In order to monitor the copper ion concentration in water bodies, a variety of detection methods have been developed, such as atomic absorption spectroscopy, atomic emission spectroscopy, inductively coupled plasma mass spectrometry and other instrumental analysis methods. However, these methods have high instrument costs, complex operations, and cumbersome maintenance. The small molecule fluorescent probe method has attracted much attention due to its excellent sensitivity, selectivity, and real-time performance. However, because most small molecule fluorescent probes are too hydrophobic and difficult to dissolve directly in water, they usually require the help of polar organic solvents such as methanol and acetonitrile to assist dissolution, which increases the environmental burden.

[0003] To meet this challenge, researchers have loaded small molecule fluorescent probes onto the surface of inorganic nanomaterials to prepare nanocomposite fluorescent probes in recent years. Heterogeneous nanocomposites can be dispersed in aqueous solutions, allowing the functional chromophores to be evenly distributed in water. Compared with small molecule fluorescent probes, they are more environmentally friendly. In addition, heterogeneous nanofluorescent probes can be used as adsorbents to remove toxic analytes, and the recovered nanofluorescent probe materials can be easily regenerated by eluting the analytes for reuse.

[0004] Traditional heavy metal adsorption materials adsorb heavy metal ions on the surface of the adsorbent by physical or chemical means, which can act to bind various heavy metal ions, resulting in non-selective adsorption of other coexisting ions. Ion-imprinted polymer materials are generally initially copolymerized by template ion coordination functional monomers and crosslinkers, followed by elution of template ions by acid solution to form specific imprinted cavities, which have high complementarity with the target guest ions in shape and size. Surface imprinting technology using sol-gel technology has also been further developed, and a thin imprinted coating film can be formed on the surface of inorganic materials. Mesoporous silica has attracted widespread attention due to its regular pore structure, high specific surface area, excellent mechanical strength and thermal stability. In view of these unique advantages, mesoporous silica is also considered to be a candidate material for the preparation of surface imprinted adsorbents with excellent performance.

[0005] Traditional surface imprinting technology is to simply introduce chelating groups to form specific imprinting cavities on the surface of high specific surface inorganic nanomaterials, and the prepared nanocomposite material can only be used for the selective adsorption of target metal ions. If the surface imprinting technology is utilized to introduce fluorescent probe molecules on the carrier surface, both the specific recognition of target ions in water and the selective fluorescence detection and adsorption removal of target ions in water can be realized, which has a good application prospect in the environmental field. Based on the above, the present invention adopts surface ion imprinting technology to prepare phenanthroline modified mesoporous silica nano fluorescent probe material, utilizes surface ion imprinting technology to realize the selective recognition of target copper ions in water, and improves the selectivity of the material to the fluorescence detection and adsorption removal of copper ions in water. Summary of the invention

[0006] In view of the disadvantage that the detection selectivity of the nanocomposite fluorescent probe for the target heavy metal ions is limited in the prior art, the present invention provides a phenanthroline-modified mesoporous silica fluorescent probe based on surface ion imprinting technology, wherein phenanthroline-imprinted cavities having high complementarity with the copper ions in shape and size are fixed on the internal pore surface and external surface of the mesoporous silica by a surface imprinting method, so as to achieve specific recognition of the target copper ions, and the structure thereof is selected from one of the general formula (I) or the general formula (II) according to the different positions of the phenanthroline substituents:

[0007]

[0008] General formula (I)

[0009]

[0010] General formula (II)

[0011] in, Refers to the internal pore surface and external surface of mesoporous silica. It is a phenanthroline imprinted cavity with high complementarity with the copper ion in shape and size, and Q is any one of 1,2-ethylene and 1,3-propylene.

[0012] The present invention further provides a method for preparing the above-mentioned phenanthroline-modified mesoporous silica fluorescent probe based on surface ion imprinting technology, comprising the following steps:

[0013] Step 1, adding equal amounts of epoxy-functionalized siloxane coupling agent and aminophenanthroline to a polar organic solvent, heating the reaction solution to 60-85° C., and magnetically stirring for 8-12 hours under nitrogen protection; after cooling to room temperature, adding a certain amount of copper nitrate as a template imprinting metal ion to the solution, wherein the amount of copper nitrate is 1 / 2 of the amount of aminophenanthroline, controlling the temperature at 25-45° C. and magnetically stirring for 8-16 hours under nitrogen protection, removing the organic solvent in the reaction system by vacuum rotary evaporation, and obtaining a phenanthroline copper complex HAP-Cu. According to the different positions of the amino substituents in the aminophenanthroline, the above synthesis step reaction formula is expressed as follows:

[0014]

[0015] Step 2: Add the HAP-Cu and mesoporous silica in step 1 to an organic solvent, perform ultrasonic dispersion, and magnetically stir at 60-90° C. for 12-24 hours under nitrogen protection; after cooling to room temperature, centrifuge the product, wash the obtained solid twice with tetrahydrofuran and then twice with ethanol, and finally vacuum dry at 80° C. to obtain a surface-modified mesoporous silica material MSN-HAP (Cu) with coordinated copper ions. The above synthesis steps are expressed as follows:

[0016]

[0017] Step 3: Add the MSN-HAP (Cu) in step 2 to an inorganic acid, and after ultrasonic dispersion, magnetic stirring is performed at room temperature for 12 to 24 hours, and the product is centrifuged. The obtained solid is repeatedly washed with deionized water until the washed aqueous solution is close to neutral, and finally vacuum dried at 80°C to obtain a phenanthroline-modified mesoporous silica fluorescent probe MSN-IIA based on surface ion imprinting technology.

[0018]

[0019]

[0020] Furthermore, in step 1, the polar organic solvent is selected from any one of acetone, methanol, anhydrous ethanol, isopropanol, anisole, tetrahydrofuran, dioxane, acetonitrile or N,N-dimethylformamide; the solid-liquid mass volume ratio of the aminophenanthroline to the polar organic mixed solution is 1:80-120 g / mL; the aminophenanthroline is selected from any one of 2-amino-1,10-phenanthroline or 5-amino-1,10-phenanthroline; the epoxy-functionalized siloxane coupling agent is selected from any one of γ-glycidyloxyethyltrimethoxysilane, γ-glycidyloxyethyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane or γ-glycidyloxypropyltriethoxysilane.

[0021] Furthermore, in step 2, the mass ratio of HAP-Cu to mesoporous silica is 1:1.0-1.5; the mesoporous silica refers to any one of SBA-15, MCM-41, SBA-16 or KIT-6 type mesoporous silica with the template removed; the organic solvent is selected from any one of acetone, methanol, anhydrous ethanol, isopropanol, anisole, tetrahydrofuran, dioxane, acetonitrile or N,N-dimethylformamide; the solid-liquid mass volume ratio of the mesoporous silica to the polar organic solvent is 1:100-150 g / mL.

[0022] Furthermore, the inorganic acid in step 3 is selected from any one of sulfuric acid, hydrochloric acid or nitric acid solution; and the mass concentration of the inorganic acid is 0.3-1.0%.

[0023] The present invention also provides a method for preparing the phenanthroline-modified mesoporous silica fluorescent probe based on surface ion imprinting technology, which can be used for selective fluorescence detection and adsorption removal of copper ions in water.

[0024] The beneficial effects of the present invention are:

[0025] 1. The mesoporous silica material modified by phenanthroline provided by the present invention has a relatively regular porous structure, a large specific surface area and good structural stability as a carrier, and when the grafted phenanthroline group forms a complex with copper ions, it will cause obvious fluorescence quenching. Therefore, compared with the traditional ligand-modified mesoporous silica material, the material provided by the present invention can be used for fluorescent quantitative detection and adsorption separation of copper ions in aqueous solution, the detection method is simple, and the material can be centrifuged and recovered.

[0026] 2. The phenanthroline-modified mesoporous silica material provided by the present invention is prepared using surface ion imprinting technology, which forms specific recognition sites on the surface of the material, thereby improving the material's selectivity for fluorescent quantitative detection and adsorption removal of copper ions in water, and solving the problem of limited selectivity of nanocomposite fluorescent probes for target ion detection in existing technologies. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0028] Figure 1 This is a scanning electron microscope photograph of MSN-IIA-1 prepared in Example 1;

[0029] Figure 2 This is a transmission electron microscope photo of MSN-IIA-1 prepared in Example 1;

[0030] Figure 3 The fluorescence emission spectra of MSN-IIA-1 prepared in Example 1 at an excitation wavelength of 278 nm in the presence of different concentrations of copper ions;

[0031] Figure 4 The fluorescence intensity (405 nm) change of MSN-IIA-1 prepared in Example 1 after adding copper ions in the presence of interfering ions;

[0032] Figure 5 The fluorescence intensity (405 nm) change of MSN-NIIA prepared in Example 4 after adding copper ions in the presence of interfering ions;

[0033] Figure 6 The adsorption amount of two ions by MSN-IIA-1 prepared in Example 1 in a binary ion system containing copper ions;

[0034] Figure 7 The adsorption amounts of two ions by MSN-NIIA prepared in Example 4 in a binary ion system containing copper ions. DETAILED DESCRIPTION

[0035] To further disclose the technical solution of the present invention, the technical solution in the embodiment of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. Based on the embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.

[0036] Embodiment 1:

[0037] The preparation of silica fluorescent probe MSN-IIA-1 based on surface ion imprinting technology is as follows:

[0038] (i) 2.36 g of γ-glycidyloxypropyltrimethoxysilane and 1.95 g of 5-amino-1,10-phenanthroline were added to 195 mL of anhydrous ethanol, the reaction solution was heated to 85° C., and magnetically stirred for 12 hours under nitrogen protection. After cooling to room temperature, 0.94 g of copper nitrate was added to the solution as a template for imprinting metal ions, and the temperature was controlled at 45° C. and magnetically stirred for 16 hours under nitrogen protection. The organic solvent in the reaction system was removed by vacuum rotary evaporation to obtain a phenanthroline copper complex HAP-Cu-1.

[0039] (ii) Add 1.0 g HAP-Cu-1 and 1.0 g SBA-15 mesoporous silica in step 1 to 150 mL anhydrous ethanol, disperse by ultrasonication, and stir magnetically at 90° C. for 24 hours under nitrogen protection. After cooling to room temperature, the product is centrifuged and the solid is washed twice with tetrahydrofuran and then twice with ethanol. Finally, it is dried in vacuo at 80° C. to obtain a mesoporous silica material MSN-HAP(Cu)-1 with surface modified phenanthroline coordinated with copper ions.

[0040] (III) 1.0 g of MSN-HAP(Cu)-1 in step 2 was added to 150 mL of 1.0% nitric acid aqueous solution, and after ultrasonic dispersion, the product was centrifuged after magnetic stirring at room temperature for 24 hours. The obtained solid was repeatedly washed with deionized water until the washed aqueous solution was close to neutral, and finally vacuum dried at 80° C. to obtain phenanthroline-modified mesoporous silica fluorescent probe MSN-IIA-1 based on surface ion imprinting technology.

[0041] Embodiment 2:

[0042] The preparation of silica fluorescent probe MSN-IIA-2 based on surface ion imprinting technology is as follows:

[0043] (i) 2.22 g of γ-glycidyloxyethyltrimethoxysilane and 1.95 g of 2-amino-1,10-phenanthroline were added to 234 mL of dioxane, the reaction solution was heated to 75° C., and magnetically stirred for 10 hours under nitrogen protection. After cooling to room temperature, 0.94 g of copper nitrate was added to the solution as a template imprinted metal ion, and magnetically stirred for 8 hours at a temperature of 30° C. under nitrogen protection. The organic solvent in the reaction system was removed by vacuum rotary evaporation to obtain a phenanthroline copper complex HAP-Cu-2.

[0044] (ii) Add 1.0 g HAP-Cu-2 and 1.5 g KIT-6 mesoporous silica in step 1 to 100 mL methanol, disperse by ultrasonication, and stir magnetically at 60 ° C for 18 hours under nitrogen protection. After cooling to room temperature, the product is centrifuged and the solid is washed twice with tetrahydrofuran and then twice with ethanol. Finally, it is dried in vacuo at 80 ° C to obtain a mesoporous silica material MSN-HAP (Cu) -2 with surface modified phenanthroline coordinated with copper ions.

[0045] (III) 1.0 g of MSN-HAP(Cu)-2 in step 2 was added to 80 mL of 0.5% nitric acid aqueous solution, and after ultrasonic dispersion, the product was centrifuged after magnetic stirring at room temperature for 18 hours. The obtained solid was repeatedly washed with deionized water until the washed aqueous solution was close to neutral, and finally vacuum dried at 80° C. to obtain phenanthroline-modified mesoporous silica fluorescent probe MSN-IIA-2 based on surface ion imprinting technology.

[0046] Embodiment 3:

[0047] The preparation of silica fluorescent probe MSN-IIA-3 based on surface ion imprinting technology is as follows:

[0048] (i) 2.78 g of γ-glycidyloxypropyltriethoxysilane and 1.95 g of 5-amino-1,10-phenanthroline were added to 156 mL of N,N-dimethylformamide, the reaction solution was heated to 60° C., and magnetically stirred for 8 hours under nitrogen protection. After cooling to room temperature, 0.94 g of copper nitrate was added to the solution as a template for imprinting metal ions, and magnetically stirred for 12 hours at a temperature of 25° C. under nitrogen protection. The organic solvent in the reaction system was removed by vacuum rotary evaporation to obtain a phenanthroline copper complex HAP-Cu-3.

[0049] (ii) Add 1.0 g HAP-Cu-3 and 1.2 g MCM-41 mesoporous silica in step 1 to 150 mL dioxane, disperse by ultrasonication, and stir magnetically at 70° C. for 12 hours under nitrogen protection. After cooling to room temperature, the product is centrifuged and the solid is washed twice with tetrahydrofuran and then twice with ethanol. Finally, it is dried in vacuo at 80° C. to obtain a mesoporous silica material MSN-HAP(Cu)-3 with surface modified phenanthroline coordinated with copper ions.

[0050] (III) 1.0 g of MSN-HAP(Cu)-3 in step 2 was added to 100 mL of 0.8% nitric acid aqueous solution, and after ultrasonic dispersion, the product was centrifuged after magnetic stirring at room temperature for 12 hours. The obtained solid was repeatedly washed with deionized water until the washed aqueous solution was close to neutral, and finally vacuum dried at 80° C. to obtain phenanthroline-modified mesoporous silica fluorescent probe MSN-IIA-3 based on surface ion imprinting technology.

[0051] Embodiment 4:

[0052] Preparation of silica fluorescent probe MSN-NIIA based on non-ionic imprinting technology, the probe material can be compared with the fluorescence detection performance of silica fluorescent probe based on ion imprinting technology. The difference between this embodiment and the above-mentioned embodiments 1 to 3 is that the mesoporous silica is first reacted with a siloxane coupling agent containing an epoxy functional group, and then reacted with aminophenanthroline to obtain a phenanthroline-modified mesoporous silica fluorescent probe. The other conditions of this embodiment refer to Example 1, and the specific steps are as follows:

[0053] (i) 2.36 g of γ-glycidyloxypropyltrimethoxysilane and 1.0 g of SBA-15 mesoporous silica were added to 150 mL of anhydrous ethanol, and ultrasonically dispersed. The mixture was magnetically stirred at 90° C. for 24 hours under nitrogen protection. After cooling to room temperature, the product was centrifuged and the solid was washed twice with tetrahydrofuran and then twice with ethanol to obtain mesoporous silica MSN-epoxy modified with epoxy functional groups.

[0054] (ii) 1.0 g of SBA-15 and 1.95 g of 5-amino-1,10-phenanthroline were added to 195 mL of anhydrous ethanol, the reaction solution was heated to 85°C, and magnetically stirred for 12 hours under nitrogen protection. After cooling to room temperature, the obtained solid was washed twice with tetrahydrofuran and then twice with ethanol, and finally dried in vacuum at 80°C to obtain the silica fluorescent probe MSN-NIIA based on non-ionic imprinting technology.

[0055] Example 5: Electron Microscope Characterization

[0056] The morphology of the silica fluorescent probe MSN-IIA-1 obtained in Example 1 was characterized by scanning electron microscopy and transmission electron microscopy.

[0057] like Figure 1 As shown in Figure 2, the SEM image shows that the material is spindle-shaped. Figure 2 As shown in the figure, the transmission electron microscopy image shows that the material has a good ordered pore structure. The results of scanning electron microscopy and transmission electron microscopy characterization show that the silica fluorescent probe MSN-IIA-1 based on surface ion imprinting technology has good structural stability. After chemical modification and treatment with acidic solution, it can still maintain the ordered and complete pore morphology of SBA-15 mesoporous silica material.

[0058] Example 6: Construction of fluorescent probe

[0059] The present invention studies the fluorescence response performance of the MSN-IIA-1 prepared in Example 1 to copper ions. The experimental temperature is 25°C, 2.0 mL of copper ion solutions of different concentrations are added to 2.0 mL of the MSN-IIA-1 stock suspension (0.2 mg / mL) prepared in Example 1, and after uniform mixing, the content of MSN-IIA-1 becomes 0.1 mg / mL, the pH value of the solution is adjusted to 6.0, and ultrasonic oscillation is used for dispersion. Finally, the suspension is quickly transferred to a quartz cuvette to record the fluorescence emission spectrum at an excitation wavelength of 278 nm.

[0060] like Figure 3 As shown in the figure, as the copper ion concentration increases from 0 mg / L to 1 mg / L, the fluorescence emission intensity of the MSN-IIA-1 dispersion decreases continuously, while the shape of the emission band in these spectra remains basically the same, and finally the fluorescence of the MSN-IIA-1 aqueous dispersion is almost completely quenched. Therefore, MSN-IIA-1 can be used as a fluorescent probe for detecting copper ions.

[0061] Example 7: Selectivity of fluorescence detection

[0062] The present invention studies the selectivity of the fluorescence detection of copper ions by MSN-IIA-1 prepared in Example 1. Wherein, the temperature in the experimental conditions is 25 ° C, and 2.0 mL of a 2 mg / L interfering ion solution is added to 2.0 mL of the MSN-IIA-1 stock suspension (0.2 mg / mL) prepared in Example 1. After uniform mixing, the content of MSN-IIA-1 becomes 0.1 mg / mL, and the concentration of interfering ions in the solution becomes 1 mg / L. The pH value of the solution is adjusted to 6.0, and ultrasonic oscillation is dispersed. Finally, the suspension is transferred to a quartz cuvette, excited at 278 nm, and the intensity of the light emitting fluorescence at 405 nm is recorded. In addition, a mixed solution of 2 mg / L interfering ions and 2 mg / L copper ions is prepared, and the above test is repeated. In order to compare the effect of surface ion imprinting technology on the selectivity of fluorescence detection, MSN-NIIA prepared based on non-ionic imprinting technology is used as a nanoprobe material to repeat the above test.

[0063] like Figure 4 As shown in the figure, other interfering metal ions cannot cause significant changes in the fluorescence intensity of the suspension at 405nm. The probe MSN-IIA-1 has a very good anti-interference ability for the recognition of copper ions. At the same time, compared with MSN-NIIA prepared by non-ionic imprinting technology ( Figure 5), after copper ions were added, the ratio of the fluorescence intensity reduction of the probe MSN-IIA-1 at 405nm was high, indicating that MSN-IIA-1 has a greater sensitivity to copper ion detection and a stronger anti-interference ability. Therefore, the surface ion imprinting technology can improve the selectivity of the nanoprobe material for fluorescent detection of copper ions in water. This characteristic makes the phenanthroline-modified mesoporous silica fluorescent probe based on surface ion imprinting technology have potential application value in the selective fluorescent detection of copper ions in water.

[0064] Embodiment 8:

[0065] The present invention studies the selective performance of the MSN-IIA-1 prepared in Example 1 for the adsorption and removal of copper ions from water. The temperature in the experimental conditions is 25°C, 50 mg of MSN-IIA-1 is added to 50 mL of a mixed solution of 100 mg / L copper ions and 100 mg / L other metal ions, and the pH value of the solution is adjusted to 6.0. Shake in a constant temperature water bath shaker for 12 hours. After the adsorption is completed, the suspension is filtered with a 0.22 μm syringe filter, and the concentrations of different metal ions in the filtrate are measured by an atomic absorption spectrometer to calculate the adsorption amount of the material for different metal ions.

[0066] like Figure 6 As shown, in the binary ion system, the adsorption amount of copper ions by MSN-IIA-1 prepared in Example 1 is significantly higher than that of another heavy metal ion. Therefore, MSN-IIA-1 exhibits a strong selective adsorption of copper ions in the binary system. Figure 7 As shown, the adsorption amount of copper ions in the mixed solution by MSN-NIIA prepared by non-ionic imprinting technology is reduced to varying degrees, and the adsorption amount of interfering ions is also increased to varying degrees. It is worth mentioning that the adsorption amount of lead ions in the mixed solution by MSN-NIIA is higher than that of copper ions, indicating that the adsorption of copper ions in the mixed solution by MSN-NIIA prepared by non-ionic imprinting technology is not selective. Therefore, the surface ion imprinting technology can improve the selectivity of the nanoprobe material for the adsorption and removal of copper ions in water. This feature makes the phenanthroline-modified mesoporous silica fluorescent probe based on surface ion imprinting technology have potential application value in the selective treatment of copper ions in water.

[0067] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A phenanthroline-modified mesoporous silica fluorescent probe based on surface ion imprinting technology, characterized in that By means of surface imprinting, a phenanthroline ligand-imprinted cavity structure having high complementarity with the copper ions in shape and size is fixed on the internal pore surface and external surface of the mesoporous silica to achieve specific recognition of the target copper ions. Depending on the position of the phenanthroline substituent, the structure is selected from one of the general formula (I) or the general formula (II): in, Refers to the internal pore surface and external surface of mesoporous silica. It is a specific imprinted cavity structure with high complementarity with the copper ion in shape and size, and Q is any one of 1,2-ethylene and 1,3-propylene.

2. A method for preparing the phenanthroline-modified mesoporous silica fluorescent probe based on surface ion imprinting technology according to claim 1, characterized in that: The preparation method comprises the following steps: Step 1, adding equal amounts of epoxy-functionalized siloxane coupling agent and aminophenanthroline to a polar organic solvent, heating the reaction solution to 60-85° C., and magnetically stirring for 8-12 hours under nitrogen protection; after cooling to room temperature, adding a certain amount of copper nitrate as a template imprinting metal ion to the solution, wherein the amount of copper nitrate is 1 / 2 of the amount of aminophenanthroline, controlling the temperature at 25-45° C. and magnetically stirring for 8-16 hours under nitrogen protection, removing the organic solvent in the reaction system by vacuum rotary evaporation, and obtaining a phenanthroline copper complex HAP-Cu. According to the different positions of the amino substituents in the aminophenanthroline, the above synthesis step reaction formula is expressed as follows: Step 2: Add the HAP-Cu and mesoporous silica in step 1 to an organic solvent, perform ultrasonic dispersion, and magnetically stir at 60-90° C. for 12-24 hours under nitrogen protection; after cooling to room temperature, centrifuge the product, wash the obtained solid twice with tetrahydrofuran and then twice with ethanol, and finally vacuum dry at 80° C. to obtain a surface-modified mesoporous silica material MSN-HAP (Cu) with coordinated copper ions. The above synthesis steps are expressed as follows: Step 3: Add the MSN-HAP (Cu) in step 2 to an inorganic acid, and after ultrasonic dispersion, magnetic stirring at room temperature for 12 to 24 hours, centrifuge the product, and repeatedly wash the obtained solid with deionized water until the washed aqueous solution is close to neutral, and finally vacuum dry at 80°C for 24 hours to obtain a phenanthroline-modified mesoporous silica fluorescent probe MSN-IIA based on surface ion imprinting technology.

3. The method for preparing a phenanthroline-modified mesoporous silica fluorescent probe based on surface ion imprinting technology according to claim 2, characterized in that: Step 1: The polar organic solvent is selected from any one of acetone, methanol, anhydrous ethanol, isopropanol, anisole, tetrahydrofuran, dioxane, acetonitrile or N,N-dimethylformamide; the solid-liquid mass volume ratio of the aminophenanthroline to the polar organic mixed solution is 1:80-120 g / mL; the aminophenanthroline is selected from any one of 2-amino-1,10-phenanthroline or 5-amino-1,10-phenanthroline; the epoxy-functionalized siloxane coupling agent is selected from any one of γ-glycidyloxyethyltrimethoxysilane, γ-glycidyloxyethyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane or γ-glycidyloxypropyltriethoxysilane.

4. The method for preparing a phenanthroline-modified mesoporous silica fluorescent probe based on surface ion imprinting technology according to claim 2, characterized in that: In step 2, the mass ratio of HAP-Cu to mesoporous silica is 1:1.0-1.5; the mesoporous silica refers to any one of SBA-15, MCM-41, SBA-16 or KIT-6 type mesoporous silica with the template removed; the organic solvent is selected from any one of acetone, methanol, anhydrous ethanol, isopropanol, anisole, tetrahydrofuran, dioxane, acetonitrile or N,N-dimethylformamide; the solid-liquid mass volume ratio of the mesoporous silica to the polar organic solvent is 1:100-150 g / mL.

5. The method for preparing a phenanthroline-modified mesoporous silica fluorescent probe based on surface ion imprinting technology according to claim 2, characterized in that: Step 3: The inorganic acid is selected from any one of sulfuric acid, hydrochloric acid or nitric acid solution; the mass concentration of the inorganic acid is 0.3-1.0%.

6. The phenanthroline-modified mesoporous silica fluorescent probe based on surface ion imprinting technology according to claim 1, characterized in that: It can be used for selective fluorescence detection and adsorption removal of copper ions in water.